Risk analysis of contamination by potentially zoonotic parasites found in public squares at Southern Brazil - Julia Somavilla Lignon; Bianca Conrad Bohm; Natália Soares Martins; Fábio Raphael Pascoti Bruhn; Felipe Geraldo Pappen; Diego Moscarelli Pinto (BMC Public Health)
Abstract Background Human beings and animals are getting closer and closer. This proximity is not limited to the home environment, as animals are also frequenters of public spaces with access to leisure areas and human recreation. As they play the role of definitive hosts for some species of potentially zoonotic helminths and protozoa, the risk of environmental contamination through their feces and the risk of infection of other animals, including humans, increases. From an epidemiological point of view, identifying possible sites at risk of infection allows us to outline adequate control and prevention methods. Therefore, the aim of this work was to carry out a risk analysis of contamination by potentially zoonotic parasites found in public squares in Southern Brazil. Methods Samples of dog feces and sand were collected in public squares in municipalities in the Pelotas microregion, south of Rio Grande do Sul, Brazil. The parasitological diagnosis was performed using the techniques of Willis-Mollay, Faust and Spontaneous sedimentation for feces and Caldwell and Caldwell for sand. The results were interpreted through descriptive data analysis and Generalized Linear Mixed Model (GLMM) with a binomial distribution and logit link function. Results In total, 4262 samples were analyzed. where 63% of positive sand samples and 50.4% of positive feces samples were parasitized by Ancylostoma spp. Of all the municipalities in the study, Cerrito, Capão do Leão and Cristal have the highest risk for the presence of parasites in the samples collected. In addition, Pelotas and Pedro Osório municipalities had more positive samples with nematode eggs; Cristal, Cerrito and Capão do Leão had more samples positive for tapeworms; Canguçu, Morro Redondo and Turuçu showed higher positivity of protozoa. Conclusion It is concluded that there is great contamination in the squares studied, by parasites with zoonotic potential, and among the identified parasites, Ancylostoma spp. is the most frequent. Furthermore, it is suggested that small municipalities are at greater risk of presenting parasites in public spaces, such as squares.